1984
DOI: 10.1152/jappl.1984.57.4.1018
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of sauna-, diuretic-, and exercise-induced hypohydration

Abstract: The physiological effects on submaximal and maximal exercise of three methods commonly used by athletes for achieving rapid weight loss were determined by measuring cardiorespiratory variables in 62 nonendurance athletes. A mean weight loss of 4.1% was achieved by those who followed either a sauna (SAU), diuretic (DIU), or exercise (ACT) protocol, compared with the average weight loss of 1.2% in the control group. At maximal exercise O2 consumption, O2 pulse, blood lactate concentration, and work load decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 20 publications
4
57
0
3
Order By: Relevance
“…Any increase in the relative workload may increase feelings of fatigue . In addition to beta-blockers, the most common drugs used were diuretics, which may compromise plasma volume or electrolyte balance during acute or chronic administration, respectively (Caldwell et al, 1984;Danzinger and Cumming, 1964). Thus, it is possible that all the treated subjects worked at a higher percentage of their maximal work capacity compared to the untreated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Any increase in the relative workload may increase feelings of fatigue . In addition to beta-blockers, the most common drugs used were diuretics, which may compromise plasma volume or electrolyte balance during acute or chronic administration, respectively (Caldwell et al, 1984;Danzinger and Cumming, 1964). Thus, it is possible that all the treated subjects worked at a higher percentage of their maximal work capacity compared to the untreated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that such dehydration is associated with impaired physiological performance (e.g. Cadwell et al 1984;Sawka and Pandolf 1990). Effects of dehydration include decreased muscular strength (Craig and Cumming 1966), reduced lactate production (Houston et al 1981), and a lowered capacity for aerobic-physical work (Saltin 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate may increase from 100 up to 150 beats per minute during sauna bathing [13,20,21], although there is no active function of skeletal muscles during the sauna bathing; which is in contrast to the training response experienced during physical activity. Indeed, it has been shown that weight loss achieved during intense physical exercise is more favorable in athletes than that achieved through the effects of sauna [22] The increase in heart rate during sauna bathing is due to reaction to the heat stress.…”
Section: Discussionmentioning
confidence: 99%